AKUNTANSI AKAD MUSYARAKAH MUTANAQISAH DALAM PEMBIAYAAN KREDIT PEMILIKAN RUMAH PADA PT.BANK MUAMALAT - Rahayu, Anik (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research is to find out both the process and the implementation in KPR montgage (House Ownership) by using musyarakah mutanaqisah contract according to applied national standard.The research methodology is using descriptive qualitative method analysis, which discusses and describes a certain condition based on the actual fast in order to get a clear description. Data on this research in based on the result of research at Muamalat Bank Tbk. Surabaya Darmo Branch.The result of this research shows that musyarakah mutanaqisah contract is the financing system(partnership). In the process of early agreement must be in accordance with the agreement between bank and potential customer according to fatwa from the board of the national syariâah. Muamalat Bank in KPR financing of musyarakah mutanaqisah is using decreases financing musyarakah and in the process of financing accounting calculation in the musyarakah mutanaqisah contract is using effective calculation system according to national standard.Keywords: Financing, contract, and Musyarakah Mutanaqisah